Memaknai Kisah Ayub Sebagai Landasan Iman Dalam Menghadapi Masalah Hidup - Semuel Linggi Topayung (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The story of Job in religious literature has become a symbol of spiritual resilience and steadfastness of faith in facing life's challenges. This article proposes a qualitative approach to understand how the story of Job can become a solid foundation for faith in facing life's problems. Through qualitative analysis of the narrative and moral message of the story of Job, this article explores the spiritual values ​​contained in it. Using qualitative research methods, this article highlights themes such as steadfastness of faith, patience, God's justice, and mental and spiritual strengthening. Through this approach, this article aims to provide a deeper understanding of the relevance of the story of Job in the context of modern human life, as well as reveal how this story can be a source of inspiration and spiritual strength for individuals facing life's trials.